Siemes, Johannes, Hermann Roesler and the Making of the Meiji State. An examination of his background and his influence on the founding of Modern Japan and the complete text of the Meiji Constitution accompanied by his personal commentaries and notes. Sophia University Press, Tokio, 1968. 252 pp., 2 ilus. - F., C. (Estudios de Asia y África, 1969)
-